A design framework of a smartphone user interface for elderly users - Salman, H.M. (Springer Science and Business Media Deutschland GmbH, 2022)
Most smartphones currently in the market have complicated user interfaces (UIs) that elderly users find difficult to use. Such difficulties often lead to triggering usability problems for the elderly when interacting with the smartphone UI. In this study, we present a design framework for fabricating smartphones with usable UIs for elderly users. We developed a framework-based prototype and experimentally compared the usability of the prototypeâs UI design with that of an Android-based UI. We considered the summative concept of usability based on the measurements of effectiveness, efficiency and satisfaction of the elderly. Twelve elderly participants were given tasks to perform on the Android and prototype, and their performances (in terms of effectiveness and efficiency) and satisfaction were measured. We measured the effectiveness using the task completion rate, the efficiency using the task completion time and the participantsâ satisfaction using the After-Scenario Questionnaire. The results showed that the design of the prototype UI outperformed the design of its Android counterpart in most aspects of the participantsâ performances and their satisfaction. The design framework has shown to be an effective tool for fabricating smartphones with usable UI designs for the elderly. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.